Conventional slab construction / Nuraini Abdullah - Abdullah, Nuraini (Universiti Teknologi MARA, Perak, 2014)
This report briefly describes the processes and methods involved in the construction of conventional slabs. It is produced based on the experience of five months on a construction site. This repo1t is divided into several sections, starting with the company background and the background of the construction project. The observation found that conventional slab construction is not as easy as it looks. It involves many complex construction processes. In this report, briefly described the methods of construction for ground floor conventional slab. Then described in more detail about the equipment and machinery used for constructing a conventional slab. During the construction process is being carried out, some of the problems associated with slab conventional methods have been identified and the report ended with some suggestions to solve a perceived problem identified. In conclusion, this report describes in detail the process and method of slab construction to readers.